Conflict and control in cortical responses to inconsistent emotional signals in a face-word Stroop - Jamieson, Graham A.; Page, Julia; Evans, Ian D.; Hamlin, Adam (Frontiers in Human Neuroscience, 2023)
Social communication is fraught with ambiguity. Negotiating the social world requires interpreting the affective signals we receive and often selecting between channels of conflicting affective information. The affective face-word Stroop (AFWS) provides an experimental paradigm which may identify core neural mechanisms underpinning essential social-affective skills. Brain imaging (fMRI) research with this paradigm identified right amygdala as driving affective conflict and left rostral anterior cingulate cortex (rACC) as the locus of conflict control. We employed electroencephalogram (EEG) and eLORETA source localisation to investigate the timing, location and sequence of control processes responding to affective-conflict during the AFWS. Unlike previous studies we designated affective word as the response target and affective face as the distractor. Reaction times showed slowed responses in high versus low control conditions corresponding to a Rabbitt type control effect rather than the previously observed Grattan effect. Control related activation occurred in right rACC 96-118ms post-stimulus corresponding to the resolution of the P1 peak in the Visual Evoked Potential (VEP). Face distractors elicit right hemisphere control while word distractors elicit left hemisphere control. Low control trials require rapid ‘booting up’ control resources observable through VEPs but not fMRI. Incongruent trial activity in right Fusiform Face Area is suppressed 118-156ms post stimulus corresponding to onset and development of the N170 VEP component. Results are consistent with a predicted sequence of rapid early amygdala activation by affective conflict, then rACC inhibition of amygdala decreasing facilitation of affective face processing. The amygdala component is inferred from fMRI but not accessible through EEG.